The anecdote of viral etiopathogenia in ameloblastoma and odontogenic keratocyst: Why don't we let it go? - Bacem A.E.O. Khalele (Elsevier, 2017)
Background: Ameloblastoma (AM) and odontogenic Keratocyst (OKC) are destructive odontogenic lesions of the gnathion. Although their exact pathogeneses are not yet totally understood, the viral etiopathogenesis in AM and KCOT has been proposed. True to syndromic keratocystic odontogenic tumor (sKCOT) and non-syndromic OKC is the high recurrence rate. Objectives: Given that shared pathways trailed by AM and by sKCOT/OKC have been suggested, this study, however, contrasts the expression of AM and OKC for viral antibodies. Method: A total of archival 80 paraffin blocks of cases of parakeratinized odontogenic keratocyst (non-syndromic KCOTs) and of ameloblastomas (n = 40 for each) were included in this study to be sectioned and stained for two immunohistochemical markers: anti-human papillomavirus and Epstein-Barr virus-encoded latent membrane protein. Results: All the submitted cases of AM and parakeratinized OKC were negative for both markers: anti-HPV and anti-LMP-1. Conclusions: Although results could have been biased, given the same ethnic group and territory examined in this study, all cases were negative for both markers. Therefore, the viral contribution to the etiopathogenesis in AM and OKC could not be established in this study.